2009
DOI: 10.1016/j.jad.2008.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Immune system dysregulation in adolescent major depressive disorder

Abstract: Background-A large body of evidence suggests that immune system dysregulation is associated with Major Depressive Disorder (MDD) in adults. This study extends this work to adolescent MDD to examine the hypotheses of immune system dysregulation in adolescents with MDD, as manifested by significantly: (i) elevated plasma levels of cytokines (interferon [IFN]-γ, tumor necrosis factor-α, interleukin [IL]-6, IL-1β, and IL-4); and (ii) Th1/Th2 cytokine imbalance shifted toward Th1 as indexed by increased IFN-γ/IL-4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 37 publications
8
127
2
1
Order By: Relevance
“…Indeed, in a handful of small case-control studies, clinically depressed adolescents have shown higher serum levels of some proinflammatory cytokines (eg, interleukin [IL]-1β and IL-6) than healthy control participants. [88][89][90] The results of larger studies of community youth have been mixed, with most but not all studies demonstrating graded associations between depressive symptoms and inflammatory biomarkers such as IL-6 and C-reactive protein (CRP). 88,[91][92][93] Findings from adults suggest that inflammation may be particularly salient in early-onset BD, 94,95 and there are preliminary findings from youth with BD.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in a handful of small case-control studies, clinically depressed adolescents have shown higher serum levels of some proinflammatory cytokines (eg, interleukin [IL]-1β and IL-6) than healthy control participants. [88][89][90] The results of larger studies of community youth have been mixed, with most but not all studies demonstrating graded associations between depressive symptoms and inflammatory biomarkers such as IL-6 and C-reactive protein (CRP). 88,[91][92][93] Findings from adults suggest that inflammation may be particularly salient in early-onset BD, 94,95 and there are preliminary findings from youth with BD.…”
Section: Inflammationmentioning
confidence: 99%
“…141 In a 2010 meta-analysis of 18 articles, 150 patients who were clinically depressed had significantly less favorable measures of autonomic dysfunction reflecting parasympathetic function than nondepressed patients; moreover, depression severity was correlated with autonomic dysfunction. Some 90,151,152 but not all 153 studies have suggested that autonomic nervous system functioning, most commonly estimated as parasympathetic withdrawal, is worse in patients with BD than in those without. Although autonomic dysfunction has been identified in the pathway between depressive disorders and CVD in adults, 154 autonomic dysfunction is less likely to lead to end-organ damage in adolescents and young adults because of the decades-long process by which CVD develops over time.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…[22][23][24] In addition, studying clinical features of mood disorders at onset in the offspring of adults with depression or BD has become a promising research approach. [25,26] Several reports have shown a relationship between: (1) the dysregulation of inflammatory markers (increased levels of IL-6, IL-1β, IL-2, IL-10, INF-α and TNF); (2) genetic variation in inflammatory genes [C-reactive protein (CRP)-gene polymorphism] and pediatric major depressive disorder; [16] (3) changes in gene expression among subjects with active mood disorders; [16] (4) preliminary evidences of an association between inflammation and suicidality in depressed youths (decreased TNF-α levels in suicidal compared to nonsuicidal depressed adolescents [27] ) as well as increased mRNA and protein expression of IL-1β, IL-6 and TNF-α in Brodmann area 10 of suicide victims relative to controls. [28] Among children and adolescents with BD, there is a high prevalence of conditions associated with inflammation, such as asthma, cardiovascular disorders, diabetes and obesity, [12] often associated with inflammatory markers, [13] including elevated high-sensitivity-C-reactive protein (hsCRP) and IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how putative biomarkers vary in a healthy population of adolescents may help in guiding the study of these blood measures in psychiatric disorders in adolescents. Examining the link between psychiatric disorders and immune system dysregulation (Gabbay et al, 2009), and the genetic contribution to these biomarkers, are both required to understand the role of plasma cytokines and vitamin D levels in adolescent psychiatric disorders.…”
mentioning
confidence: 99%